2010
DOI: 10.1038/nn.2660
|View full text |Cite
|
Sign up to set email alerts
|

Wild-type and mutant SOD1 share an aberrant conformation and a common pathogenic pathway in ALS

Abstract: Many mutations confer upon copper/zinc superoxide dismutase-1 (SOD1) one or more toxic function(s) that impair motor neuron viability and cause familial amyotrophic lateral sclerosis (FALS). Using a conformation-specific antibody that detects misfolded SOD1 (C4F6), we demonstrate that oxidized WT-SOD1 and mutant-SOD1 share a conformational epitope that is not present in normal WT-SOD1. In a subset of human sporadic ALS (SALS) cases, motor neurons in the lumbosacral spinal cord displayed striking C4F6 immunorea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
662
2
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 610 publications
(704 citation statements)
references
References 50 publications
32
662
2
8
Order By: Relevance
“…These results parallel those reported by Bosco et al (33), in which either a different human mutant SOD1 (H46R) or hydrogen peroxide-treated WT human SOD1 had similar inhibitory effects specifically on anterograde transport in the axoplasm assay, whereas WT human SOD1 had little or no effect. The present data suggest that a variety of oligomeric forms of mutant SOD1 species may be toxic to transport, potentially including monomeric forms, but the dynamic nature of the noncrosslinked material precludes conclusions about which species might be most toxic in that context.…”
Section: G85r Sod1-yfp But Not Wt Sod1-yfp Inhibits Anterograde Fastsupporting
confidence: 90%
“…These results parallel those reported by Bosco et al (33), in which either a different human mutant SOD1 (H46R) or hydrogen peroxide-treated WT human SOD1 had similar inhibitory effects specifically on anterograde transport in the axoplasm assay, whereas WT human SOD1 had little or no effect. The present data suggest that a variety of oligomeric forms of mutant SOD1 species may be toxic to transport, potentially including monomeric forms, but the dynamic nature of the noncrosslinked material precludes conclusions about which species might be most toxic in that context.…”
Section: G85r Sod1-yfp But Not Wt Sod1-yfp Inhibits Anterograde Fastsupporting
confidence: 90%
“…The phenotype of this mice recapitulates several clinical and histopathological features of both familial and sporadic forms of the human disease [3]. Moreover, it has been recently reported that alterations of the SOD1 protein are also related to sporadic ALS cases [4], increasing the interest in the study of transgenic animals.…”
Section: Introductionmentioning
confidence: 64%
“…This model recapitulates most relevant clinical and histopathological features of both familial and sporadic forms of the human disease [3]. It is also of relevance that alterations of the SOD1 protein have been reported in sporadic ALS patients [4], increasing the interest of this murine model. Several mechanisms have been implicated as contributors to MN death in ALS, such as glutamate excitotoxicity, oxidative stress, protein misfolding, mitochondrial defects, impaired axonal transport, and inflammation [5,6].…”
Section: Introductionmentioning
confidence: 71%